Pelatihan Pemanfaatan Platform Video Conference untuk Mendukung Pembelajaran Hybrid bagi Siswa SMP Negeri 6 Palangka Raya - Nova Noor Kamala Sari; Ressa Priskila; Widiatry; Viktor Handrianus Pranatawijaya; Putu Bagus Adidyana Anugrah Putra; Efrans Christian; Septian Geges; Novera Kristianti; Tomas Leonardo; Purmasari (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2026)
The community service activity entitled “Training on the Use of Video Conference Platforms for Students of SMP Negeri 6 Palangka Raya” was conducted with the main objective of enhancing students’ digital literacy, particularly in utilizing online learning applications such as Google Meet and Zoom. The identified problem was the students’ limited technical skills in operating these platforms, which could hinder their active participation in both hybrid and online learning. To address this issue, the program was designed as a hands-on training that included the introduction of basic features, simulations of virtual classrooms, and guidance on digital ethics in online interactions. Through this approach, students not only acquired fundamental technical skills but also improved their confidence in participating in online learning and developed a sense of responsibility in using technology. Therefore, this activity provides a tangible contribution to supporting students’ readiness in facing the increasingly digitalized educational landscape